STEMnesia: Workshop Integrating STEM Education by Local Potential Indonesia–America in Science Learning Process [STEMnesia: Workshop Integrasi Pendidikan STEM dengan Potensi Lokal Indonesia-Amerika dalam Pembelajaran IPA] - Andinisa Rahmaniar; Abdul Latip; Dudung Abdurrahman; Shinta Purnamasari; Wiwit Yuli Lestari; Iskandar Kanta Dinata; Hani Agnesti; Refa Fatmah (Jurnal Pengabdian Isola, 2023)
The community service activities carried out aim to provide workshops to science teachers in Garut Regency regarding STEM education. STEM education raised in this workshop is related to the perspective of local potential in Indonesia and America. STEMnesia activities consist of 3 main activities: 1) Providing material by a team of science education lecturers at Garut University and Illnois University lecturers, 2) Workshop activities in the form of group work between participants. 3) presentation activities and providing feedback. In general, teachers have been able to develop STEM learning tools well and provide positive responses to these STEMnesia activities.Kegiatan pengabdian kepada masyarakat yang dilaksanakan bertujuan untuk memberikan workshop kepada guru IPA di Kabupaten Garut mengenai pendididkan STEM. Pendidikan STEM yang diangkat dalam workshop ini dikaitakan dengan prespective potensi lokal Indonesia dan Amerika. Kegiatan STEMnesia terdiri dari 3 kegiatan utama: 1) Pemberian materi oleh tim dosen pendidikan IPA Universitas Garut dan Dosen Illnois University, 2) Kegiatan workshop dalam bentuk kerja kelompok antar peserta. 3) kegiatan presentasi dan pemberian umpan balik. Secara umum guru sudah mampu mengembangkan perangkat pembelajaran STEM dengan baik dan memberikan respon positif terhadap kegiatan STEMnesia ini